Community cinema as a strategy against violence in Latin America: Experience in a vulnerable urban periphery - Baltar Moreno, Adolfo; Bernabé Fraguas, Javier (Street Art & Urban Creativity, 2025)
Based on a real filming experience, this text offers a reflection on the possibilities that community cinema offers when used in urban contexts affected by insecurity, poverty and social stigmatization. It first addresses the growing importance acquired by this type of cinema in Latin America in recent decades and its link with other cinematographic and epistemological currents typical of this continent. Below are the production phases of a community short film made in a popular neighborhood on the outskirts of Cartagena de Indias (Colombia) in 2023. This form of cinematographic expression is revealed as an innovative strategy of sociocultural and artistic intervention useful to combat violence, strengthen the social fabric of the territories, overthrow cultural prejudices, promote intergenerational and intercultural dialogue and consolidate the cultural identity and collective memory of those who have no voice